Poluição difusa por fósforo devido a aplicação de aplicação de água residuária da suinocultura sob condição de chuva simulada - Dieter, Jonathan (2010)
The western region of Paraná is characterized as a wetland, where the average monthly rainfall exceeded 100 mm. In this region the pig is a very intense activity which causes environmental and public health due to the significant volume of waste generated. Most of the properties is common to allocate the liquid and solid wastes to the soil in the period between harvests as a fertilizer and water reuse in agriculture. However, this practice associated with the humid climate of the region enhances the diffuse pollution in order to impact, particularly surface water depending on the process of runoff, leading to eutrophication of water bodies and lower layer of fertile soil in the region. Thus, it is necessary to study the nutrient losses in runoff water and sediments carried by considering the application of different rates of pig manure in the soil and also with different intensities of rain with characteristic erosive. The results showed that the concentration of available soil phosphorus in the soil Erdöd is dependent on the application rate of swine wastewater and that during the flow is greater superfical transferecia soluble phosphorus to water early in the runoff.